Hubungan Dukungan Keluarga Dengan Perilaku Anak Yang Kecanduan Game Online Di Kelurahan Malawei Kota Sorong - Hardiyanti, Rina; Simon, Merlis; Wahdania, Nurul (Jurnal Keperawatan Muhammadiyah, 2024)
Online gaming is the excessive and compulsive use of computer or video games that results in social and emotional problems. Indonesia is the country with the third largest number of video game players in the world. The aim of this research is to determine the relationship between family support and the behavior of children addicted to online games in the district of Malawei Sorong City. This type of research is quantitative research with an analytical survey research design. Population this study involved 36 childrean aged 6-12 years. The research sample consisted of 36 respondents. The sampling technique used was total sampling. The research instrument was a questionnaire and the statistical test used was the Chi Square test. The results of the research that has been carried out show that respondents who receive family support tend to have good behavior by (38,9%) with statistical test showing a P Value of 0.008 meaning that there is a relationship between family support and behavior of children who are addicted to online games in the district of Malawei Sorong City. Suggestions for parents to do more increase supervision and limit children's use of gadgets and accustom children to more involved in many social activities.